Binder composition for secondary battery, slurry composition for secondary battery, functional layer for secondary battery, separator for secondary battery, electrode for secondary battery, and secondary battery

By using a binder composition of core-shell particles composed of specific polymers, the problems of reduced adhesion and lithium metal precipitation caused by migration of bonding materials in secondary batteries are solved, and better battery performance and safety are achieved sex.

CN115003713BActive Publication Date: 2025-02-25ZEON CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202180009508.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-28
Filing Date
2021-02-03
Publication Date
2025-02-25
Estimated Expiration
2041-02-03

AI Technical Summary

Technical Problem

In existing secondary batteries, the migration phenomenon of bonded materials leads to a decrease in adhesion, affecting battery performance and circulation characteristics, and also has safety hazards for precipitation of lithium metal.

Method used

Using a binder composition containing core-shell particles composed of specific polymers, by adjusting the composition and structure of the polymer, the migration of the bonding material is inhibited, the adhesion between the layer and the substrate is improved, and the precipitation of lithium metal is reduced. .

Benefits of technology

The excellent adhesion between the middle layer of the secondary battery and the substrate is achieved, the circulation characteristics of the battery are improved, and the precipitation of lithium metal is effectively suppressed, thereby improving the safety and reliability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003747665180000381
    Figure BDA0003747665180000381
  • Figure BDA0003747665180000391
    Figure BDA0003747665180000391
  • Figure BDA0003747665180000401
    Figure BDA0003747665180000401
Patent Text Reader

Abstract

The present invention provides a secondary battery binder composition, which can achieve excellent adhesion between a layer obtained by using the binder composition and a substrate, and obtain a secondary battery with good cycle characteristics. The secondary battery binder composition comprises a polymer and a solvent, wherein the polymer is a core-shell particle having a core portion composed of a polymer (a1) and a shell portion composed of a polymer (a2), wherein the polymer (a2) comprises a monofunctional unsaturated carboxylic acid ester monomer unit, one or more monomer units selected from a monofunctional unsaturated carboxylic acid monomer unit and a monofunctional unsaturated sulfonic acid monomer unit, a monomer unit having two or more vinyl functional groups, and an aromatic vinyl monomer unit in a specified amount, and relative to 1 mol of the above-mentioned monomer unit having two or more vinyl functional groups, the above-mentioned monomer unit selected from one or more monomer units of a monofunctional unsaturated carboxylic acid monomer unit and a monofunctional unsaturated sulfonic acid monomer unit is 0.1 mol or more and 15000 mol or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a binder composition for a secondary battery, a slurry composition for a secondary battery, a functional layer for a secondary battery, a separator for a secondary battery, an electrode for a secondary battery, and a secondary battery. Background Art

[0002] Non-aqueous secondary batteries, represented by lithium-ion secondary batteries, are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are used in a wide range of applications. Secondary batteries generally have battery components such as electrodes (positive and negative electrodes) and separators that separate the positive and negative electrodes to prevent short circuits between the positive and negative electrodes.

[0003] Usually, as a separator of a secondary battery, a separator having an adhesive layer containing a bonding material, a porous membrane layer containing a bonding material and non-conductive particles as functional particles on a separator substrate can be used. In addition, as an electrode of a secondary battery, an electrode having an electrode composite material layer containing a bonding material and electrode active material particles as functional particles on a current collector can be used, and an electrode having an electrode composite material layer on a current collector and further having the above-mentioned bonding layer and porous membrane layer can be used.

[0004] In order to further improve the performance of secondary batteries, attempts have been made to improve the binder composition containing a binder, and a technique for improving adhesion by using a binder composed of core-shell particles has been proposed.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent document 1: International Publication No. 2016 / 039067;

[0008] Patent Document 2: Japanese Patent Application Publication No. 2015-201444;

[0009] Patent document 3: Japanese Patent Application Publication No. 2006-513554;

[0010] Patent Document 4: Japanese Patent Application Publication No. 2013-073921;

[0011] Patent document 5: Japanese Patent Application Laid-Open No. 6-302797;

[0012] Patent Document 6: International Publication No. 2017 / 110901;

[0013] Patent document 7: International Publication No. 2017 / 188055;

[0014] Patent Document 8: International Publication No. 2018 / 043200;

[0015] Patent document 9: Japanese Patent Application Publication No. 11-025989;

[0016] Patent Document 10: Japanese Patent Application Publication No. 2013-182765. Summary of the invention

[0017] Problem that the invention aims to solve

[0018] However, in the above-mentioned prior art, there is the following problem in the manufacturing process of each of the above-mentioned layers: the phenomenon called migration, in which the binding material formed by the core-shell particles easily moves to the surface of the layer, occurs. When migration occurs, the binding material tends to be present near the surface, while the amount of the binding material near the interface with the substrate decreases, the adhesion between the substrate and the layer decreases, and the battery performance of the secondary battery, especially the cycle characteristics, is reduced.

[0019] Here, when repeated charge and discharge cycles are performed, the problem of lithium metal precipitation is known as a problem unique to lithium ion secondary batteries. The precipitation of lithium metal on the negative electrode during charge and discharge may cause a short circuit, and from the perspective of improving safety and reliability, it is required to strictly suppress the precipitation of lithium metal.

[0020] The object of the present invention is to provide a binder composition containing core-shell particles, which can achieve excellent adhesion between a layer obtained by using the binder composition and a substrate in the production process of a separator, electrode, etc. of a secondary battery, and can obtain a secondary battery with good cycle characteristics.

[0021] Solutions for solving problems

[0022] The present inventors have made intensive studies with a view to solving the above-mentioned problems, focusing on suppressing the migration of the adhesive material, and have completed the present invention.

[0023] That is, the object of the present invention is to advantageously solve the above-mentioned problems. The binder composition for secondary batteries of the present invention comprises a polymer and a solvent.

[0024] The polymer is a core-shell type particle having a core portion consisting of the polymer (a1) and a shell portion consisting of the polymer (a2),

[0025] The polymer (a2) comprises 50.0% by mass or more and 89.9% by mass or less of a monofunctional unsaturated carboxylic acid ester monomer unit, 10.0% by mass or more and 49.9% by mass or less of one or more monomer units selected from a monofunctional unsaturated carboxylic acid monomer unit and a monofunctional unsaturated sulfonic acid monomer unit, 0.1% by mass or more and 10.0% by mass or less of a monomer unit having two or more vinyl functional groups, and 5.0% by mass or less of an aromatic vinyl monomer unit,

[0026] The amount of the at least one monomer unit selected from the group consisting of a monofunctional unsaturated carboxylic acid monomer unit and a monofunctional unsaturated sulfonic acid monomer unit is 0.1 mol or more and 15,000 mol or less per mol of the monomer unit having two or more vinyl functional groups.

[0027] Here, the "core-shell type particle" refers to a particle having a multilayer structure (core-shell structure) in which the surface of a core portion is covered with a shell portion.

[0028] “Containing a monomer unit” means “a polymer obtained using the monomer contains a repeating unit derived from the monomer”.

[0029] The "unsaturated carboxylic acid ester monomer" refers to an unsaturated carboxylic acid ester containing an ethylenically unsaturated bond.

[0030] The "unsaturated carboxylic acid monomer" refers to an unsaturated carboxylic acid containing an ethylenically unsaturated bond, including anhydrides thereof.

[0031] "Monofunctional unsaturated carboxylic acid ester monomer" refers to an unsaturated carboxylic acid ester containing one ethylenically unsaturated bond.

[0032] "Monofunctional unsaturated carboxylic acid monomer" refers to an unsaturated carboxylic acid containing one ethylenically unsaturated bond, including anhydrides thereof.

[0033] "Monofunctional unsaturated sulfonic acid monomer" refers to an unsaturated sulfonic acid containing one ethylenically unsaturated bond, including anhydrides thereof.

[0034] In the secondary battery using the binder composition of the present invention, the mechanism by which excellent adhesion is achieved between the layer obtained using the binder composition and the substrate is presumed as follows.

[0035] When the shell of the core-shell particles is introduced into one or more monomer units selected from monofunctional unsaturated carboxylic acid monomer units and monofunctional unsaturated sulfonic acid monomer units, these units are soluble in the water usually contained in the binder composition, and are charged in the composition, and the molecular chains constituting the shell are stretched by electrical repulsion, so that the shell can be solubilized. At this time, by making the shell simultaneously have monofunctional unsaturated carboxylic acid ester monomer units, the solubility of the shell can be improved by utilizing the polarity of the ester bond in the monomer unit. It is speculated that the molecular chain stretches and the solubilized shell will suppress the migration of the core-shell particles as a binding material during the manufacture of the layer (for example, electrode composite material layer, porous film layer, etc.) of the secondary battery. Moreover, it is speculated that by suppressing the migration, excellent adhesion is achieved between the layer obtained using the binder composition and the substrate.

[0036] On the other hand, when only monofunctional unsaturated carboxylic acid ester monomer units and one or more monomer units selected from monofunctional unsaturated carboxylic acid monomer units and monofunctional unsaturated sulfonic acid monomer units are introduced into the shell portion, when the secondary battery is assembled and the electrolyte is injected, the electrolyte insoluble amount of the core-shell particles as the binding material is reduced, and the cycle characteristics of the secondary battery may deteriorate. In the present invention, it is speculated that the reduction in the electrolyte insoluble amount can be suppressed by introducing a specified amount of monomer units having two or more vinyl functional groups.

[0037] Moreover, at this time, it is speculated that by making the ratio of monomer units having two or more vinyl functional groups to one or more monomer units selected from monofunctional unsaturated carboxylic acid monomer units and monofunctional unsaturated sulfonic acid monomer units within a specified range, the two aspects of migration inhibition brought about by the extension of the molecular chain of the shell in the aqueous phase and the reduction of the insoluble amount of the electrolyte can be achieved.

[0038] According to the above mechanism, it is inferred that in the secondary battery using the binder composition of the present invention, excellent adhesion is achieved between the layer obtained using the binder composition and the substrate, and even after repeated charge and discharge cycles, the adhesion can be suppressed from decreasing. Moreover, it is inferred that in the secondary battery using the binder composition of the present invention, good cycle characteristics can be exerted.

[0039] In addition to the above advantages, by using the binder composition of the present invention in the manufacture of a lithium ion secondary battery, a lithium ion secondary battery in which the precipitation of lithium metal is significantly suppressed can be obtained. It is speculated that the suppression of the precipitation of lithium metal is due to the excellent liquid retention of the core-shell particles serving as the binding material for the electrolyte and the fact that the binding material can be prevented from being biased by suppressing migration.

[0040] The present invention relates to the above-mentioned binder composition for secondary batteries, wherein the tetrahydrofuran (THF) insoluble content of the above-mentioned polymer (a1) is 40% or more and 97% or less. By using the polymer (a1) having the THF insoluble content within the above-mentioned range for the core portion, it is possible to impart an appropriate elastic modulus to the core-shell particles as a binder, obtain good film-forming properties between the particles, and also fully improve the adhesion to the substrate.

[0041] Here, the amount of THF insoluble components can be measured by the method described in Examples of this specification.

[0042] The present invention relates to the above-mentioned binder composition for secondary batteries, wherein the ratio of the mass of the above-mentioned polymer (a1) to the mass of the above-mentioned polymer (a2) is 95 / 5 or less and 5 / 95 or more. The core part of the core-shell type particle having the mass ratio of the above-mentioned polymer (a1) to the mass of the above-mentioned polymer (a2) within the above-mentioned range is fully covered by the shell part, and migration can be fully suppressed.

[0043] The present invention relates to the above-mentioned binder composition for secondary batteries, wherein the inertia radius of the above-mentioned core-shell particles is greater than 10nm and less than 1000nm. The molecular chains of the shell portion of the core-shell particles with an inertia radius within the above-mentioned range are fully extended, and migration can be fully suppressed. In addition, the number of particles with excellent liquid retention of the electrolyte is relatively sufficient, and the partial existence of the electrolyte is suppressed, especially in the case of lithium ion secondary batteries, the precipitation of lithium metal can be fully prevented, so it is advantageous.

[0044] Here, the radius of inertia can be measured by the method described in the examples of this specification.

[0045] Furthermore, the present invention relates to a slurry composition for a secondary battery having the above-mentioned binder composition for a secondary battery. The present invention relates to the above-mentioned slurry composition for a secondary battery containing non-conductive particles, and further relates to the above-mentioned slurry composition for a secondary battery containing an electrode active material.

[0046] Furthermore, the present invention relates to a secondary battery functional layer formed using the above-mentioned secondary battery slurry composition. The present invention relates to a secondary battery separator, which has a secondary battery functional layer formed using the above-mentioned secondary battery slurry composition containing non-conductive particles on a separator substrate, and further, the present invention relates to a secondary battery electrode, which has a secondary battery functional layer formed using the above-mentioned secondary battery slurry composition containing electrode active material particles on a current collector.

[0047] Furthermore, the present invention relates to a secondary battery having the above-mentioned secondary battery functional layer. The present invention relates to a secondary battery having the above-mentioned secondary battery separator, and further relates to a secondary battery having the above-mentioned secondary battery electrode.

[0048] Effects of the Invention

[0049] According to the secondary battery binder composition of the present invention, in the manufacturing process of the separator, electrode, etc. of the secondary battery, excellent adhesion is achieved between the layer obtained by using the binder composition and the substrate, and a secondary battery with good cycle characteristics can be obtained. When the secondary battery binder composition of the present invention is used, even after repeated charge and discharge cycles, the decrease in adhesion can be suppressed.

[0050] Furthermore, in addition to the above-mentioned advantages, the lithium ion secondary battery using the binder composition of the present invention has significantly suppressed precipitation of lithium metal. DETAILED DESCRIPTION

[0051] The embodiments of the present invention are described in detail below.

[0052] The secondary battery binder composition of the present invention can be used for the production of secondary batteries (for example, non-aqueous secondary batteries such as lithium ion secondary batteries), and can be used to prepare, for example, the secondary battery slurry composition of the present invention.

[0053] The slurry composition for secondary batteries of the present invention can be used to form any functional layer (e.g., electrode composite material layer, porous membrane layer, adhesive layer) that performs electron transfer, reinforcement or bonding functions in secondary batteries (e.g., non-aqueous secondary batteries such as lithium ion secondary batteries).

[0054] The functional layer for secondary batteries of the present invention is formed from the slurry composition for secondary batteries of the present invention.

[0055] Furthermore, the separator for a secondary battery and the electrode for a secondary battery of the present invention have the functional layer for a secondary battery of the present invention.

[0056] Furthermore, the secondary battery of the present invention (for example, a non-aqueous secondary battery such as a lithium ion secondary battery) comprises at least one of the secondary battery functional layer, the secondary battery separator and the secondary battery electrode of the present invention.

[0057] <Binder composition for secondary battery>

[0058] The binder composition for secondary batteries of the present invention contains a polymer and a solvent.

[0059] [polymer]

[0060] The binder composition for secondary batteries of the present invention contains a polymer. The polymer is a core-shell type particle having a core part composed of a polymer (a1) and a shell part composed of a polymer (a2).

[0061] (Polymer (a1))

[0062] The core portion composed of the polymer (a1) is not particularly limited, and a known polymer as a binder can be used.

[0063] -THF-insoluble content of polymer (a1)-

[0064] The THF insoluble content of polymer (a1) is preferably 40% or more, and is preferably 97% or less. The THF insoluble content is more preferably 45% or more, and is further preferably 50% or more, and is further preferably 95% or less, and is further preferably 93% or less.

[0065] The amount of THF insoluble components can be adjusted according to the type and amount of monomers used to prepare the polymer (a1). Alternatively, an aqueous dispersion of a polymer having the same composition as the polymer (a1) may be prepared and the amount of THF insoluble components thereof may be measured to obtain the amount of THF insoluble components of the polymer (a1).

[0066] - Composition of polymer (a1) -

[0067] The polymer (a1) may be a polymer having any composition, and examples thereof include a polymer containing an unsaturated carboxylic acid ester monomer unit and an unsaturated carboxylic acid monomer unit.

[0068] The unsaturated carboxylic acid ester that can form the unsaturated carboxylic acid ester monomer unit is not particularly limited, and examples thereof include: methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, tert-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, 2-ethylhexyl acrylate and other octyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, stearyl acrylate and other alkyl acrylates (e.g., alkyl esters having 1 to 20 carbon atoms, preferably alkyl esters having 1 to 10 carbon atoms); Methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, amyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate such as 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, alkyl methacrylate such as stearyl methacrylate (for example, alkyl esters having 1 to 20 carbon atoms, preferably alkyl esters having 1 to 10 carbon atoms), and the like.

[0069] Among them, from the viewpoint of polymerization stability and formation of a core-shell structure, methyl methacrylate, ethyl methacrylate, and n-butyl acrylate are preferred, and a combination of methyl methacrylate and n-butyl acrylate is more preferred.

[0070] The unsaturated carboxylic acid ester monomer unit may be used alone or in combination of two or more at any ratio.

[0071] The unsaturated carboxylic acid that can form the unsaturated carboxylic acid monomer is not particularly limited, and examples thereof include acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, etc. The unsaturated dicarboxylic acid may be an acid anhydride.

[0072] Among them, acrylic acid, methacrylic acid, and itaconic acid are more preferred, and acrylic acid and methacrylic acid are further preferred, from the viewpoint of polymerization stability and formation of a core-shell structure.

[0073] In the case of polymer (a1) being 100.0% by mass, the unsaturated carboxylic acid ester monomer unit is preferably more than 20.0% by mass, more preferably more than 30.0% by mass, and in addition, preferably less than 99.9% by mass, more preferably less than 90.0% by mass. If it is above the above lower limit, the shell portion is fully coated with the core portion and can be fixed to the core portion, and the foaming of the binder composition and the slurry composition can be suppressed. In addition, if it is below the above upper limit, the insoluble amount in the electrolyte is sufficient, and good cycle characteristics can be achieved.

[0074] The unsaturated carboxylic acid monomer unit is preferably 0.1% by mass or more, more preferably 1.0% by mass or more, and preferably 5.0% by mass or less, and more preferably 4.5% by mass or less. If it is above the lower limit, the core-shell type particles are fully stabilized and can achieve good adhesion with the substrate. In addition, if it is below the upper limit, the shell portion can fully cover the core portion, and the foaming of the binder composition and the slurry composition can be suppressed.

[0075] The polymer containing unsaturated carboxylic acid ester monomer units and unsaturated carboxylic acid monomer units can contain other monomer units. As monomers that can form other monomer units, aliphatic conjugated diene monomers such as 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), and 2,3-dimethyl-1,3-butadiene; aromatic vinyl monomers such as styrene, styrene sulfonic acid and its salts, α-methylstyrene, butoxystyrene, and vinylnaphthalene can be cited. Other monomer units can be 10.0% by mass or less.

[0076] In order to reduce the insoluble amount of the electrolyte, as other monomer units, it is possible to contain, for example, aliphatic conjugated diene monomer units. For example, polymer (a1) can be composed of unsaturated carboxylic acid ester monomer units, unsaturated carboxylic acid monomer units and aliphatic conjugated diene monomer units. At this time, the aliphatic conjugated diene monomer can be more than 5.0 mass %, preferably more than 10.0 mass %, in addition, the aliphatic conjugated diene monomer can be less than 50.0 mass %, preferably less than 45.0 mass %. For the amount of unsaturated carboxylic acid ester monomer units and unsaturated carboxylic acid monomer units, the above-mentioned exemplification and preferred ranges can be applied.

[0077] As polymer (a1), in addition to the above-mentioned polymers, aliphatic conjugated diene polymers such as polybutadiene and polyisoprene, aromatic vinyl-aliphatic conjugated diene copolymers such as styrene-butadiene polymers (SBR), styrene-butadiene-styrene polymers (SBS), cyanide vinyl-conjugated diene copolymers such as acrylonitrile-butadiene polymers (NBR), hydrogenated SBR, hydrogenated NBR, etc. can be used. In addition, the polymers described in Japanese Patent No. 6520720 can be used.

[0078] (Shell portion composed of polymer (a2))

[0079] The shell portion is composed of a polymer (a2), which includes 50.0% by mass or more and 89.9% by mass or less of a monofunctional unsaturated carboxylic acid ester monomer unit, 10.0% by mass or more and 49.9% by mass or less of one or more monomer units selected from a monofunctional unsaturated carboxylic acid monomer unit and a monofunctional unsaturated sulfonic acid monomer unit, 0.1% by mass or more and 10.0% by mass or less of a monomer unit having two or more vinyl functional groups, and 5.0% by mass or less of an aromatic vinyl monomer unit. The content of each monomer unit is based on 100.0% by mass of the polymer (a2).

[0080] In the polymer (a2), the amount of one or more monomer units selected from the monofunctional unsaturated carboxylic acid monomer units and monofunctional unsaturated sulfonic acid monomer units is 0.1 mol or more and 15,000 mol or less per mol of the monomer units having two or more vinyl functional groups.

[0081] -Amount of each monomer unit-

[0082] When the monofunctional unsaturated carboxylic acid ester monomer unit is less than 50.0 mass %, the shell part cannot fully cover the core part, the fixation of the core part is insufficient, and the adhesive composition and the slurry composition become easy to foam. On the other hand, when the monofunctional unsaturated carboxylic acid ester monomer is greater than 89.9 mass %, the shell part becomes difficult to dissolve in water, the molecular chain of the shell part does not extend, the migration inhibition ability is reduced, and it becomes difficult to achieve high adhesion.

[0083] When the content of one or more monomer units selected from monofunctional unsaturated carboxylic acid monomer units and monofunctional unsaturated sulfonic acid monomer units (hereinafter also referred to as "monofunctional unsaturated carboxylic acid and / or sulfonic acid monomer units") is less than 10.0% by mass, the shell becomes less soluble in water, the molecular chain of the shell does not extend, the migration inhibition ability is reduced, and it becomes difficult to achieve high adhesion. On the other hand, when the monofunctional unsaturated carboxylic acid and / or sulfonic acid monomer units are greater than 49.9% by mass, the shell cannot fully cover the core, the fixation of the core is insufficient, and the binder composition and the slurry composition become easy to foam.

[0084] The content of the monofunctional unsaturated carboxylic acid and / or sulfonic acid monomer units is preferably 13.0% by mass or more, more preferably 16.0% by mass or more, and is preferably 49.0% by mass or less, more preferably 48.0% by mass or less.

[0085] When the monomer unit with two or more vinyl functional groups is less than 0.1% by mass, the solubility of the core-shell particles as a bonding material in the electrolyte becomes high, the function as a bonding material is weakened, and the peel strength after the cycle characteristics and the cycle test is reduced. In addition, since the liquid retention of the electrolyte is reduced, the precipitation of lithium metal can not be fully suppressed in the case of a lithium ion secondary battery. On the other hand, when the monomer unit with two or more vinyl functional groups is greater than 10.0% by mass, the cross-linked structure in the shell increases, the shell becomes insoluble in water, the molecular chain of the shell does not stretch, the migration inhibition ability is reduced, and it becomes difficult to achieve high adhesion. The monomer unit with two or more vinyl functional groups is preferably more than 0.2% by mass, more preferably more than 0.5% by mass, in addition, preferably less than 8.0% by mass, more preferably less than 3.0% by mass.

[0086] When the aromatic vinyl monomer unit is greater than 5.0 mass %, the shell cannot fully cover the core, and the adhesive composition and the slurry composition become prone to foaming. The aromatic vinyl monomer unit is preferably 4.0 mass % or less, more preferably 2.0 mass % or less, and can be 0.0 mass %.

[0087] In the range that does not impair the effect of the present invention, polymer (a2) can contain other monomer units, preferably by 50.0 mass % or more and 89.9 mass % or less of monofunctional unsaturated carboxylic acid ester monomer units, 10.0 mass % or more and 49.9 mass % or less of monofunctional unsaturated carboxylic acid and / or sulfonic acid monomer units, 0.1 mass % or more and 10.0 mass % or less of monomer units with two or more vinyl functional groups and 5.0 mass % or less (can be 0.0 mass %) of aromatic vinyl monomer units.

[0088] When the monofunctional unsaturated carboxylic acid and / or sulfonic acid monomer unit is less than 0.1 mole relative to 1 mole of monomer units with two or more vinyl functional groups, the molecular chain of the shell portion does not extend, the migration inhibition ability is reduced, and it becomes difficult to achieve high adhesion. In addition, when the monofunctional unsaturated carboxylic acid and / or sulfonic acid monomer unit is greater than 15000 moles relative to 1 mole of monomer units with two or more vinyl functional groups, the solubility of the core-shell particles in the electrolyte as a bonding material becomes higher, the function as a bonding material is weakened, and the peel strength after the cycle characteristics and the cycle test is reduced. Relative to 1 mole of monomer units with two or more vinyl functional groups, the monofunctional unsaturated carboxylic acid and / or sulfonic acid monomer unit is preferably more than 0.15 mole, more preferably more than 0.25 mole, in addition, preferably less than 14000 moles, more preferably less than 13500 moles.

[0089] -Monofunctional unsaturated carboxylic acid ester monomer unit-

[0090] The monofunctional unsaturated carboxylic acid ester capable of forming the monofunctional unsaturated carboxylic acid ester monomer unit can be a monocarboxylic acid ester or a polycarboxylic acid ester, and from the viewpoint of forming a core-shell structure, a monocarboxylic acid ester is preferred, and acrylates, methacrylates, etc. are more preferred. As the ester, an alkyl ester can be mentioned, and from the viewpoint of polymerization stability and forming a core-shell structure, an alkyl ester having 1 to 20 carbon atoms can be used, and an alkyl ester having 1 to 10 carbon atoms is preferred.

[0091] Specific examples include: methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, tert-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, 2-ethylhexyl acrylate and other octyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, stearyl acrylate and the like; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, 2-ethylhexyl methacrylate and other octyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, stearyl methacrylate and the like.

[0092] Among them, methyl methacrylate, ethyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, and the like are preferred from the viewpoint of forming a core-shell structure.

[0093] The monofunctional unsaturated carboxylic acid ester monomer unit may be used alone or in combination of two or more at any ratio.

[0094] -Monofunctional unsaturated carboxylic acid and / or sulfonic acid monomer units-

[0095] The monofunctional unsaturated carboxylic acid that can form the monofunctional unsaturated carboxylic acid monomer unit can be a monocarboxylic acid or a polycarboxylic acid. From the viewpoint of molecular chain extension of the shell portion, a monocarboxylic acid is preferred, acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, and itaconic acid are more preferred, and acrylic acid, methacrylic acid, and itaconic acid are further preferred.

[0096] Examples of the monofunctional unsaturated sulfonic acid that can form the monofunctional unsaturated sulfonic acid monomer include vinyl sulfonic acid, p-styrene sulfonic acid, (meth)allyl sulfonic acid, and the like, and p-styrene sulfonic acid is preferred.

[0097] The monofunctional unsaturated carboxylic acid and / or sulfonic acid monomer units may be in the form of a salt, and examples thereof include alkali metal salts (Na salts, K salts, etc.), alkaline earth metal salts (Mg salts, etc.), and ammonium salts.

[0098] These monofunctional unsaturated carboxylic acid and / or sulfonic acid monomer units may be used alone or in combination of two or more at any ratio.

[0099] -Monomer units having two or more vinyl functional groups-

[0100] Regarding the polymer (a2), the "monomer unit having two or more vinyl functional groups" does not include a monomer unit corresponding to the "aromatic vinyl monomer unit".

[0101] The number of vinyl functional groups in the monomer unit having two or more vinyl functional groups may be two or more, and is preferably two or more and ten or less, and more preferably two or more and six or less, from the viewpoint of the solubility of the shell part in water.

[0102] Examples of monomers having two or more vinyl functional groups that can form monomer units having two or more vinyl functional groups include aliphatic dienes such as 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), and 2,3-dimethyl-1,3-butadiene; vinyl ethers or allyl ethers of unsaturated carboxylic acids such as allyl acrylate, allyl methacrylate, vinyl acrylate, and vinyl methacrylate; and acrylic acid esters or methacrylic acid esters of polyols such as ethylene glycol dimethacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, tetraethylene glycol diacrylate, ethoxylated isocyanuric acid triacrylate, ethoxylated glycerol triacrylate, ditrimethylolpropane tetraacrylate, ethoxylated pentaerythritol tetraacrylate, dipentaerythritol polyacrylate, and dipentaerythritol hexaacrylate.

[0103] Among them, ethylene glycol dimethacrylate, 1,3-butadiene, ethoxylated pentaerythritol tetraacrylate, and the like are preferred from the viewpoint of the solubility of the shell part in water.

[0104] The monomer unit having two or more vinyl functional groups may be used alone or in combination of two or more at any ratio.

[0105] -Aromatic vinyl monomer unit-

[0106] Regarding the polymer (a2), the "aromatic vinyl monomer unit" does not include a monomer unit corresponding to any of the "monofunctional unsaturated carboxylic acid monomer unit" and the "monofunctional unsaturated sulfonic acid monomer unit".

[0107] When an aromatic vinyl monomer unit is present, examples of the monomer capable of forming the aromatic vinyl monomer include styrene, α-methylstyrene, butoxystyrene, and vinylnaphthalene.

[0108] The aromatic vinyl monomer unit may be used alone or in combination of two or more at any ratio.

[0109] -Molecular weight of polymer (a2)-

[0110] The weight average molecular weight of polymer (a2) is preferably 10000 or more, more preferably 30000 or more, and preferably 10000000 or less, more preferably 4500000 or less. If it is within the above range, the migration of the shell portion can be fully suppressed, good adhesion can be achieved, and in the binder composition and the slurry composition, the core-shell particles as the binder material are fully dispersed, and good cycle characteristics can be achieved.

[0111] The weight average molecular weight can be measured using the measurement method described in Examples of the present specification.

[0112] (Core-shell particles)

[0113] The core-shell type particles have a core portion composed of a polymer (a1) and a shell portion composed of a polymer (a2).

[0114] -Mass ratio of polymer (a1) to polymer (a2)-

[0115] In the core-shell type particles, the ratio of the mass of polymer (a1) to the mass of polymer (a2) ((mass of a1) / (mass of a2)) is preferably 95 / 5 or less, more preferably 90 / 10 or less, further preferably 87 / 13 or less, and is preferably 5 / 95 or more, more preferably 10 / 90 or more, and more preferably 13 / 87 or more.

[0116] -Inertia radius of core-shell particles-

[0117] The inertia radius of the core-shell particles is preferably 10 nm or more, more preferably 30 nm or more, and even more preferably 50 nm or more, and is preferably 1000 nm or less, more preferably 800 nm or less, and even more preferably 600 nm or less.

[0118] -Method for producing core-shell particles-

[0119] The method for producing the core-shell type particles is not particularly limited, but from the viewpoint of obtaining the core-shell type particles in a simple manner, emulsion polymerization, solution polymerization, bulk polymerization, suspension polymerization, and the like are preferred.

[0120] As the emulsion polymerization method, the following method can be mentioned: in an aqueous solvent, in the presence of an emulsifier and a polymerization initiator, the monomers forming the polymer (a1) are subjected to free radical polymerization to obtain the polymer (a1), and then the monomers forming the polymer (a2) are further added and polymerized. From the viewpoint of covering the outer surface of the core part with the shell part, the monomers forming the polymer of the shell part are preferably supplied to the polymerization system in multiple times or continuously.

[0121] The emulsifier is not particularly limited, and examples thereof include anionic surfactants such as sodium dodecylbenzenesulfonate and sodium dodecyl sulfate (sodium lauryl sulfate); and cationic surfactants such as octadecylamine acetate.

[0122] The emulsifier may be used alone or in combination of two or more at any ratio.

[0123] The polymerization initiator is not particularly limited, and examples thereof include peroxides such as tert-butyl peroxy-2-ethylhexanoate, potassium persulfate, ammonium persulfate, and cumene peroxide; and azo compounds such as 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)-propionamide) and 2,2'-azobis(2-amidinopropane) hydrochloride.

[0124] The polymerization initiator may be used alone or in combination of two or more at any ratio.

[0125] A chain transfer agent may be used in the reaction. The chain transfer agent is not particularly limited, but is preferably an alkyl mercaptan, and more preferably tert-dodecyl mercaptan.

[0126] Water can be used as the aqueous solvent, and a hydrophilic solvent other than water can be mixed within the range that the monomers used to prepare the core-shell type particles can be dissolved or dispersed. Examples of the hydrophilic solvent include alcohols such as methanol, ethanol, n-propanol, and isopropanol; ketones such as acetone and methyl ethyl ketone; polyalkylene glycols such as ethylene glycol, diethylene glycol, and propylene glycol; alkyl ethers of polyalkylene glycols; lactams such as N-methyl-2-pyrrolidone, and the like.

[0127] From the viewpoint of making the shell part charged and using its repulsive force to extend the molecular chain, the core-shell type particles are preferably subjected to pH adjustment using a basic compound after polymerization. When an aqueous solvent is used, the pH of the reaction solution after polymerization is generally about 0.2 to 6, and pH adjustment using a basic compound is generally equivalent to a neutralization operation.

[0128] From the viewpoint of slurry stability, the pH is preferably adjusted to 4 or more and 9 or less. As the alkaline compound, for example, organic amines such as methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, 2-aminoethanol, and 2-dimethylaminoethanol; inorganic alkaline compounds such as ammonia (water), sodium hydroxide, potassium hydroxide, and lithium hydroxide; quaternary ammonium hydroxides such as tetramethylammonium hydroxide, tetra-n-butylammonium hydroxide, and trimethylbenzylammonium hydroxide, etc. Among them, inorganic alkaline compounds such as sodium hydroxide and potassium hydroxide are preferred. The alkaline compound can be used alone or in combination of two or more in any ratio.

[0129] Preferably, the ratio of the viscosity after the pH adjustment of the binder composition to the viscosity before the pH adjustment (viscosity after adjustment / viscosity before adjustment) is 1.5 times or more to manufacture core-shell particles, more preferably 1.6 times or more, and the upper limit is not particularly limited, usually 500 times or less. If within the above range, the molecular chain of the shell portion is fully extended, migration is fully suppressed, and the core-shell particles as the binding material in the binder composition and the slurry composition are fully dispersed, and good cycle characteristics can be achieved.

[0130] [Solvent]

[0131] The secondary battery binder composition of the present invention comprises a solvent. The solvent can be an aqueous solvent, and water, a mixed solvent of water and a hydrophilic organic solvent can be cited, wherein water is preferred. As an aqueous solvent, the description (including exemplification, preferred examples) in the manufacturing process of core-shell particles can be applied. The aqueous solvent used in the manufacture of core-shell particles can be directly used.

[0132] [Manufacturing of adhesive composition, etc.]

[0133] The secondary battery binder composition of the present invention can be directly prepared by dispersing the core-shell particles obtained by emulsion polymerization in an aqueous solvent, or by adjusting pH, removing unreacted monomers, desolvating, etc. as needed. The method of removing unreacted monomers and desolvating is not particularly limited, and examples thereof include heating, reduced pressure distillation, and a combination thereof.

[0134] The binder composition preferably has an electrolyte insoluble amount of 50% or more, more preferably 55% or more. The upper limit is 100%, and the electrolyte insoluble amount can be 100%. If it is within the above range, the core-shell particles maintain the core-shell structure, achieve sufficient adhesion, and maintain good cycle characteristics.

[0135] Here, the amount of insoluble electrolyte can be measured by the method described in Examples of this specification.

[0136] The binder composition can include a binder material other than core-shell particles, and relative to 100 parts by mass of the binder material, the core-shell particles can advantageously be more than 5 parts by mass, preferably more than 20 parts by mass. As a binder material, only core-shell particles can also be used. As a binder material other than core-shell particles, for example: aliphatic conjugated diene polymers such as polybutadiene, polyisoprene, styrene-butadiene polymers (SBR), aromatic vinyl aliphatic conjugated diene copolymers such as styrene-butadiene-styrene polymers (SBS), cyanide vinyl-conjugated diene copolymers such as acrylonitrile-butadiene polymers (NBR), hydrogenated SBR, hydrogenated NBR, etc. can be used.

[0137] The adhesive composition may further contain thickeners, wetting agents, conductive additives, reinforcing materials, leveling agents, electrolyte additives, defoamers, etc. within the range not impairing the effects of the present invention. These components may be used alone or in combination of two or more in any ratio.

[0138] The solid content concentration of the adhesive composition is not particularly limited, and can be, for example, 5 mass % or more and 70 mass % or less.

[0139] <Slurry composition for secondary battery>

[0140] The slurry composition for secondary batteries of the present invention is a composition for forming any functional layer in a secondary battery (e.g., a non-aqueous secondary battery such as a lithium ion secondary battery), and includes a binder composition for secondary batteries of the present invention, and can also include functional particles and other components. Since the binder composition for secondary batteries of the present invention is included, the functional layer with excellent adhesion can be obtained by applying the slurry composition for secondary batteries of the present invention to, for example, a substrate and drying it.

[0141] [Binder composition]

[0142] The amount of the binder composition for secondary batteries of the present invention in the slurry composition is not particularly limited and can be set according to the functional layer.

[0143] When the slurry composition is used to prepare an electrode composite material layer, the amount of the binder (core-shell particles and any binder) of the binder composition can be 0.5 parts by mass or more and 15 parts by mass or less in terms of solid content relative to 100 parts by mass of the electrode active material particles.

[0144] When the slurry composition is used to prepare a porous membrane layer, the binder composition may contain 0.5 to 30 parts by mass of the binder (core-shell particles and any binder) based on solid content per 100 parts by mass of the non-conductive particles.

[0145] [Functional particles]

[0146] The slurry composition may contain functional particles according to the desired functional layer. When the functional layer is an electrode composite material layer, the functional particles may be electrode active material particles, and when the functional layer is a porous membrane layer, the functional particles may be non-conductive particles.

[0147] (Electrode active material particles)

[0148] The electrode active material particles are not particularly limited, and examples thereof include particles formed of known electrode active materials used in secondary batteries. For example, regarding the electrode composite material layer of a lithium ion secondary battery, examples thereof include particles formed of the following electrode active materials.

[0149] - Positive electrode active material -

[0150] The positive electrode active material blended in the positive electrode composite material layer of the positive electrode of the lithium ion secondary battery is not particularly limited, and examples thereof include compounds containing transition metals, such as transition metal oxides, transition metal sulfides, and composite metal oxides of lithium and transition metals.

[0151] Here, examples of the transition metal include Ti, V, Cr, Mn, Fe, Co, Ni, Cu, and Mo.

[0152] Specifically, lithium-containing cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium-containing nickel oxide (LiNiO2), Co-Ni-Mn lithium-containing composite oxides, Ni-Mn-Al lithium-containing composite oxides, Ni-Co-Al lithium-containing composite oxides, olivine lithium iron phosphate (LiFePO4), olivine lithium manganese phosphate (LiMnPO4), Li 1+x Mn 2-x O4 (0<X<2) represented by lithium-excess spinel compounds, Li[Ni 0.17 Li 0.2 Co 0.07 Mn 0.56 ]O2、LiNi 0.5 Mn 1.5 O4, etc.

[0153] The positive electrode active material may be used alone or in combination of two or more at any ratio.

[0154] - Negative electrode active material -

[0155] The negative electrode active material blended in the negative electrode composite material layer of the negative electrode of the lithium ion secondary battery is not particularly limited, and examples thereof include carbon-based negative electrode active materials, metal-based negative electrode active materials, and negative electrode active materials in combination thereof.

[0156] Here, the carbon-based negative electrode active material refers to an active material with a carbon-based skeleton that can be inserted with lithium (also called "doping"), and examples thereof include: coke, mesocarbon microbeads (MCMB), mesophase pitch-based carbon fibers, pyrolysis vapor-grown carbon fibers, phenolic resin sintered bodies, polyacrylonitrile-based carbon fibers, quasi-isotropic carbon, furfuryl alcohol resin sintered bodies (PFA), hard carbon and other carbonaceous materials; graphite materials such as natural graphite and artificial graphite, etc.

[0157] The metal-based negative electrode active material refers to an active material containing a metal, generally referring to an active material containing an element capable of inserting lithium in the structure, and having a theoretical capacity per unit mass of 500 mAh / g or more when inserting lithium, and examples thereof include: lithium metal, single metal capable of forming a lithium alloy (e.g., Ag, Al, Ba, Bi, Cu, Ga, Ge, In, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, etc.), and their oxides, sulfides, nitrides, silicides, carbides, phosphides, etc. Furthermore, oxides such as lithium titanate can be cited.

[0158] The negative electrode active material may be used alone or in combination of two or more at any ratio.

[0159] (Non-conductive particles)

[0160] The non-conductive particles are not particularly limited, and examples thereof include known non-conductive particles used for secondary batteries.

[0161] The non-conductive particles may be inorganic particles or organic particles, and inorganic particles are usually used. Among them, materials that are stable in the use environment of the secondary battery and are electrochemically stable are preferred.

[0162] From this point of view, non-conductive particles are preferably oxide particles such as alumina, hydrated alumina (boehmite), silicon oxide, magnesium oxide (magnesia), calcium oxide, titanium oxide (Titania), BaTiO3, ZrO, and alumina-silicon dioxide composite oxides; nitride particles such as aluminum nitride and boron nitride; covalently bonded crystal particles such as silicon and diamond; insoluble ionic crystal particles such as barium sulfate, calcium fluoride, and barium fluoride; clay particles such as talc and montmorillonite, etc. These particles can be subjected to element replacement, surface treatment, solid solution, etc. as needed.

[0163] The non-conductive particles may be used alone or in combination of two or more at any ratio.

[0164] [Other ingredients]

[0165] The slurry composition may contain other components within a range that does not impair the effects of the present invention. As other components, the description (including examples and preferred examples) in the binder composition can be applied.

[0166] The other components may be used alone or in combination of two or more at any ratio.

[0167] [Manufacturing of slurry composition, etc.]

[0168] The method for producing the slurry composition is not particularly limited.

[0169] For example, when the slurry composition is used to produce an electrode composite material layer, the binder composition, the electrode active material particles, and other components used as necessary are mixed in the presence of a solvent to produce the slurry composition.

[0170] When the slurry composition is used for producing a porous membrane layer, the binder composition, the non-conductive particles, and other components used as necessary are mixed in the presence of a solvent to produce the slurry composition.

[0171] When the slurry composition is used to form the adhesive layer, the adhesive composition may be used as it is or diluted with a solvent to form a slurry composition, or the adhesive composition and other components used as necessary may be mixed in the presence of a solvent to produce the slurry composition.

[0172] The solvent used in the preparation of the slurry composition also includes the solvent in the binder composition. The solvent is not particularly limited, and examples thereof include water, alcohol, ketone, etc. The mixing method is not particularly limited, and a known stirrer, disperser, etc. can be used.

[0173] <Functional layer for secondary batteries>

[0174] The functional layer for secondary batteries of the present invention is a layer that performs functions such as electron transfer, reinforcement or bonding in a secondary battery (for example, a non-aqueous secondary battery such as a lithium-ion secondary battery). Examples thereof include an electrode composite material layer that transfers electrons via an electrochemical reaction, a porous membrane layer that improves heat resistance and strength, an adhesive layer that improves adhesion, etc.

[0175] The functional layer of the present invention is formed by the slurry composition for secondary batteries of the present invention, and can be formed by, for example, applying the slurry composition on, for example, a substrate and drying it. The slurry composition for secondary batteries of the present invention contains the binder composition for secondary batteries of the present invention, so that excellent adhesion can be achieved between the functional layer formed by the slurry composition and the substrate.

[0176] [Base material]

[0177] The substrate to which the slurry composition is applied is not particularly limited. When forming an electrode composite material layer, a current collector may be used as a substrate, and the slurry composition may be applied on the current collector and dried to form a layer.

[0178] When forming a porous membrane layer or an adhesive layer, a separator substrate or an electrode substrate can be used as a substrate, and a slurry composition can be applied on the substrate and dried to form a layer.

[0179] Alternatively, the slurry composition may be applied to the surface of a release substrate and dried to form a functional layer, the release substrate may be peeled off, and the functional layer peeled off from the release substrate may be used as a self-supporting film in the production of a secondary battery.

[0180] (current collector)

[0181] The current collector is not particularly limited, and a material having electrical conductivity and electrochemical durability can be used, and examples thereof include current collectors formed of, for example, iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. Among them, copper foil is particularly preferred as a current collector for the negative electrode. In addition, aluminum foil is particularly preferred as a current collector for the positive electrode. The material for the current collector can be used alone or in combination of two or more in any ratio.

[0182] (Spacer Base Material)

[0183] The spacer substrate is not particularly limited, and known spacer substrates such as organic spacer substrates can be cited. The organic spacer substrate is a porous member formed of an organic material, and microporous films or nonwoven fabrics containing polyolefin resins such as polyethylene and polypropylene, aromatic polyamide resins, etc. can be cited. From the viewpoint of excellent strength, microporous films and nonwoven fabrics made of polyethylene are preferred.

[0184] (Electrode substrate)

[0185] The electrode substrate (positive electrode substrate and negative electrode substrate) is not particularly limited, and examples thereof include an electrode substrate in which an electrode composite material layer including electrode active material particles and a binder is formed on the above-mentioned current collector.

[0186] The electrode active material particles and the binding material contained in the electrode composite material layer are not particularly limited, and the electrode active material particles described in the slurry composition and the binding materials described in the binder composition except the core-shell particles can be used. As the electrode composite material layer in the electrode substrate, the functional layer of the present invention can be used.

[0187] [Formation of functional layer]

[0188] The method for forming the functional layer on a substrate such as a current collector, a separator substrate, or an electrode substrate is not particularly limited, and examples thereof include the following methods.

[0189] 1) A method of applying the slurry composition of the present invention to the surface of a substrate (the surface on the electrode composite material layer side in the case of an electrode substrate) and then drying it;

[0190] 2) A method of immersing a substrate in the slurry composition of the present invention and then drying the substrate; and

[0191] 3) A method in which the slurry composition of the present invention is applied onto a release substrate, dried to produce a functional layer, and the obtained functional layer is transferred to the surface of the substrate.

[0192] Among these, the method 1) is preferred because the thickness of the functional layer can be easily controlled. The method 1) includes, in detail, a step of applying the slurry composition on a substrate (coating step) and a step of drying the slurry composition applied on the substrate to form a functional layer (drying step).

[0193] (Coating process)

[0194] The method for applying the slurry composition to the substrate is not particularly limited, and examples thereof include a doctor blade method, a reverse roll coating method, a direct roll coating method, a gravure method, an extrusion method, and a brush coating method.

[0195] (Drying process)

[0196] The method for drying the slurry composition on the substrate is not particularly limited, and a known method can be used, such as drying with warm air, hot air, or low-humidity air; vacuum drying; and drying by irradiation with infrared rays, electron beams, or the like.

[0197] When the electrode composite material layer is prepared as the functional layer, it is preferred that the electrode composite material layer be subjected to a press treatment using a die press, a roll press, or the like after the drying step.

[0198] <Secondary battery>

[0199] The secondary battery of the present invention (for example, a non-aqueous secondary battery such as a lithium ion secondary battery) has a positive electrode, a negative electrode, a separator and an electrolyte, and at least any one of the positive electrode, the negative electrode and the separator has a functional layer for the secondary battery of the present invention. The secondary battery of the present invention can also be manufactured using the separator for the secondary battery of the present invention and / or using the electrode for the secondary battery of the present invention as one or both of the positive electrode and the negative electrode. The positive electrode, the negative electrode and the separator that do not have the functional layer for the secondary battery of the present invention are not particularly limited, and known positive electrodes, negative electrodes and separators can be used.

[0200] [Electrolyte]

[0201] The electrolyte is not particularly limited, and an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent can be cited. As a supporting electrolyte for a lithium ion secondary battery, lithium salts can be cited, for example: LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. Among them, from the viewpoint of being easily soluble in a solvent and showing a high degree of dissociation, LiPF6, LiClO4, CF3SO3Li are preferred. The electrolyte can be used alone or in combination of two or more in any ratio. There is usually a tendency that the higher the supporting electrolyte with a higher degree of dissociation, the higher the lithium ion conductivity, so the lithium ion conductivity can be adjusted according to the type of supporting electrolyte.

[0202] The organic solvent used in the electrolyte is not particularly limited as long as it is an organic solvent that can dissolve the supporting electrolyte. As organic solvents for lithium-ion secondary batteries, there can be cited: carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), ethyl methyl carbonate (EMC), vinylene carbonate (VC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide, etc. A mixed solution of these solvents can be used. Among them, carbonates are preferred because of their high dielectric constant and wide stable potential region. Generally, there is a tendency that the lower the viscosity of the solvent used, the higher the lithium ion conductivity, so the lithium ion conductivity can be adjusted by the type of solvent.

[0203] The concentration of the electrolyte in the electrolytic solution can be adjusted appropriately. A known additive may be added to the electrolytic solution.

[0204] [Manufacturing of secondary batteries, etc.]

[0205] The secondary battery of the present invention can be manufactured by, for example, the following method: overlapping the positive electrode and the negative electrode with a separator, winding, folding, etc., placing them in a battery container, injecting an electrolyte into the battery container, and sealing. In this case, at least one of the positive electrode, the negative electrode, and the separator has a functional layer for the secondary battery of the present invention.

[0206] If necessary, porous metal mesh, fuse, PTC element and other overcurrent protection elements, guide plates and the like can be placed in the battery container to prevent the pressure inside the battery from rising and overcharging and discharging. The shape of the battery is not particularly limited, and examples thereof include coin-shaped, button-shaped, sheet-shaped, cylindrical, square, flat and the like.

[0207] Example

[0208] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.

[0209] In a polymer produced by copolymerizing a plurality of monomers, unless otherwise specified, the ratio of a repeating unit (monomer unit) formed by polymerizing a certain monomer in the above polymer is usually consistent with the ratio (feed ratio) of the certain monomer in all monomers used for polymerization of the polymer.

[0210] In the Examples and Comparative Examples, the following measurements and evaluations (1) to (11) were performed.

[0211] (1) Weight average molecular weight of the shell

[0212] (2) Amount of the binder composition that is insoluble in the electrolyte

[0213] (3) Viscosity ratio of adhesive composition before and after neutralization

[0214] (4) Amount of THF-insoluble components in core polymer

[0215] (5) Inertia radius of core-shell particles

[0216] (6) Foaming of slurry composition

[0217] (7) Peel strength of electrode

[0218] (8) Peel strength of spacer coating layer

[0219] (9) Cycle characteristics of secondary batteries

[0220] (10) Peel test after cycle test

[0221] (11) Lithium metal precipitation test

[0222] (1) Weight average molecular weight of the shell

[0223] A solution of the polymer of the shell alone (pH 8.0) was prepared, and its weight average molecular weight was measured by gel permeation chromatography (GPC) as the weight average molecular weight of the shell. The method for preparing the solution of the polymer of the shell alone is described below.

[0224] The determination is carried out as follows. First, a separate shell polymer is added to about 5 mL of eluent to a solid content concentration of about 0.5 g / L, a stirrer is placed at room temperature (25°C), and a magnetic stirrer is used to stir at 300 rpm for 10 minutes to dissolve it. After visually confirming the dissolution, filter with a 0.45 μm filter to prepare a sample for determination. Then, by making a standard curve with a standard substance, the weight average molecular weight as a standard substance conversion value is calculated.

[0225] The measurement conditions are as follows.

[0226] <Measurement conditions>

[0227] Column: Showa Denko Co., Ltd., product name "Shodex OHpak (SB-G, SB-807HQ, SB-806MHQ)"

[0228] Eluent: 0.1M Tris buffer (with 0.1M potassium chloride added)

[0229] Flow rate: 0.5mL / min

[0230] Sample concentration: 0.05 g / L (solid content concentration)

[0231] Injection volume: 200 μL

[0232] Column temperature: 40°C

[0233] Detector: Differential refractometer RI (manufactured by Tosoh Corporation, product name "RI-8020")

[0234] Standard substance: Monodisperse pullulan (manufactured by Showa Denko K.K.)

[0235] (2) Amount of the binder composition that is insoluble in the electrolyte

[0236] The adhesive composition was applied to a substrate made of Teflon (registered trademark) and dried for 24 hours at a relative humidity of 50% and a temperature of 23°C to 25°C to form a film with a thickness of 0.5±0.3mm. The film was dried in a vacuum dryer at a temperature of 60°C for 10 hours, and then cut into 2mm square film pieces, and the obtained film pieces were accurately weighed. (Mass W1)

[0237] Next, the obtained membrane was added to 10 mL of a 1.0M LiPF6 solution (solvent: a mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio), containing an additive: 2% by volume of vinyl carbonate (solvent ratio)) at a temperature of 60°C. The membrane was confirmed to be immersed in the electrolyte as a whole and stored at a temperature of 60°C for 72 hours.

[0238] Then, the membrane was taken out of the container with tweezers, placed in another container, and 10 mL of diethyl carbonate was added. After confirming that the entire membrane was immersed in the liquid, it was left to stand at a temperature of 25° C. for 2 hours for cleaning.

[0239] Then, the membrane was taken out of the container with tweezers, placed in another container, and 10 mL of ethanol was added to confirm that the entire membrane was immersed in the liquid, and then washed by leaving it at a temperature of 25° C. for 2 hours.

[0240] Take out the membrane, place it on a wipe paper, and dry it in a fume hood for 2 hours. Then, put the membrane into a vacuum dryer, reduce the pressure to below -0.09 MPa at 25°C, dry it for more than 2 hours, and weigh it accurately. (Mass W2)

[0241] The insoluble amount of the electrolyte solution is calculated from the mass W1 and the mass W2 according to the following formula.

[0242] Insoluble electrolyte content (%) = W2 / W1×100

[0243] (3) Viscosity ratio of adhesive composition before and after neutralization

[0244] The viscosity was measured using a B-type viscometer under the conditions of a temperature of 25° C., a spindle speed of 60 rpm, and a spindle rotation time of 60 seconds.

[0245] The unneutralized solution after polymerization was diluted with ion exchange water to a solid content concentration of 10%, and the viscosity was measured. (Viscosity η1)

[0246] Next, while stirring the post-polymerization solution, an alkaline aqueous solution was added to neutralize it to pH 8.0. The solid content concentration was adjusted to 10%, and the viscosity after neutralization was measured. (Viscosity η2)

[0247] The viscosity ratio η3 of the adhesive composition before and after neutralization was determined from the viscosity η1 and the viscosity η2 using the following formula.

[0248] n j =n2 / n1

[0249] The higher the value of the viscosity ratio η3 is, the more the migration of the adhesive composition is suppressed.

[0250] (4) Amount of THF-insoluble components in core polymer

[0251] The core polymer solution is applied to the substrate and dried for 24 hours in an environment with a humidity of 50% and a temperature of 22-25°C to form a film with a thickness of about 0.3 mm. The film is cut into 2-3 mm squares and the obtained film is accurately weighed. (Mass w0)

[0252] The membrane was immersed in 75 mL of tetrahydrofuran (THF) at 25°C for 24 hours. The membrane was then vacuum dried at 105°C for 3 hours and accurately weighed to obtain the mass of the insoluble component (mass w1).

[0253] The amount of THF insoluble components was calculated from the mass w0 and the mass w1 by the following formula.

[0254] THF insoluble content (mass %) = (w1 / w0) × 100

[0255] (5) Inertia radius of core-shell particles

[0256] The radius of inertia is determined by using a field-flow fractionation (FFF) device connected to a multi-angle light scattering (MALS) detector to make a Zimm Plot using a static light scattering method. The FFF device is a device that allows a sample solution to pass through a gap (channel) of more than 100 μm and less than 500 μm and can apply a field when passing through the channel.

[0257] 50 μL of a measurement sample containing core-shell particles was injected into an FFF device connected to a MALS detector, and static light scattering measurement was performed at a flow rate of 1.0 mL / min.

[0258] The measurement conditions are as follows.

[0259] <Measurement conditions>

[0260] MALS detector: Made by Postnova, product name "PN3621 MALS"

[0261] FFF device: Made by Postnova, product name "AF2000"

[0262] RI detector: Made by Postnova, product name "PN3150 RI"

[0263] Channel: Polyethersulfone membrane 10kDa

[0264] Developing solution: Phosphate buffer (1mM)

[0265] Measurement sample: 100 μL of core-shell particles diluted to 1% with ion-exchanged water was diluted with 900 μL of pH 7.4 phosphate buffer (1 mM) to adjust the solid content to 0.1%.

[0266] (6) Foaming of slurry composition

[0267] 100g of the secondary battery slurry composition was placed in a container with an inner diameter of 6cm, and mixed at 2000rpm for 5 minutes at a temperature of 25°C using a disperser equipped with a 3cm diameter sawtooth disk turbine blade. Then, the composition was placed in a pressurized box, and the pressure in the box was made 0.1Mpa with nitrogen, and maintained for 3 minutes. After taking it out, the number of bubbles with a diameter of 0.1mm or more existing on the surface of the composition was counted using a 20x magnifying glass.

[0268] A: Less than two

[0269] B: Two or more but less than six

[0270] C: Six or more but less than ten

[0271] D: More than ten

[0272] The smaller the number of bubbles, the more foaming of the composition is suppressed.

[0273] (7) Peel strength of electrode

[0274] Cut a rectangular test piece of 100 mm in length and 10 mm in width from the electrode (negative or positive electrode). Fix the test piece on the test bench with the electrode composite material layer facing up. After sticking a transparent tape (transparent tape specified in JIS Z1522) on the surface of the electrode composite material layer fixed with the test piece, peel off the transparent tape from one end of the test piece at a speed of 50 mm / min in a 180° direction, and measure the stress during peeling. Perform the same measurement 5 times, take the average value as the peel strength, and judge using the following criteria.

[0275] A: Peel strength is 10N / m or more

[0276] B: Peel strength is 8 N / m or more and less than 10 N / m

[0277] C: Peel strength is 4 N / m or more and less than 8 N / m

[0278] D: Peel strength less than 4N / m

[0279] The larger the value, the better the adhesion to the substrate.

[0280] (8) Peel strength of spacer coating layer

[0281] Cut a rectangular test piece of 100 mm in length and 10 mm in width from the spacer coated with the functional layer. Fix a transparent tape (transparent tape specified in JIS Z1522) on the test bench in advance. After attaching the obtained test piece to the transparent tape with the functional layer of the spacer facing downward, stretch one end of the spacer in the vertical direction at a tensile speed of 100 mm / min and measure the stress during peeling. Perform 3 measurements, and use the average value as the peel strength of the spacer coating layer, and evaluate according to the following criteria.

[0282] A: Peel strength is 100N / m or more

[0283] B: Peel strength is 80 N / m or more and less than 100 N / m

[0284] C: Peel strength is 60 N / m or more and less than 80 N / m

[0285] D: Peel strength less than 60N / m

[0286] The larger the value, the better the adhesion to the substrate.

[0287] (9) Cycle characteristics of secondary batteries

[0288] After the laminated cell type lithium ion secondary battery was injected with electrolyte, it was left to stand at 25°C for 24 hours and then charged to a cell voltage of 4.35 V and discharged to a cell voltage of 3.0 V using a 0.1C constant current method to measure the initial capacity C0.

[0289] Furthermore, in an environment of temperature 45°C, charging to a battery cell voltage of 4.35V was repeated by a constant current method at 1.0C, and discharging to a battery cell voltage of 3.0V was repeated by a constant current method in the same charging mode, and the capacity C2 after 100 cycles was measured.

[0290] The capacity retention rate C3 was calculated from the capacity C0 and the capacity C2 by the following formula.

[0291] C3(%)=(C2 / C0)×100

[0292] A: Capacity retention rate C3 is more than 95%

[0293] B: Capacity retention rate C3 is 90% or more and less than 95%

[0294] C: Capacity retention rate C3 is 80% or more and less than 90%

[0295] D: Capacity retention rate C3 is less than 80%

[0296] The larger the value, the better the cycle characteristics.

[0297] (10) Peel test after cycle test

[0298] The battery cell after the test of the cycle characteristics of the secondary battery in (9) above was disassembled in a glove box, and the electrode (negative electrode or positive electrode) was recovered. The recovered electrode was immersed in a solvent (a mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 30 / 70 (volume ratio)) for 10 minutes so that the electrode composite material layer was in contact with the solvent, and then immersed in ethyl methyl carbonate for 10 minutes. The immersed electrode was taken out and dried in a fume hood in a drying room for 2 hours.

[0299] Cut out a rectangular test piece of 100 mm in length and 10 mm in width from the obtained electrode (negative electrode or positive electrode). Fix the test piece on the test bench with the electrode composite material layer facing up. After sticking a transparent tape (transparent tape specified in JIS Z1522) on the surface of the electrode composite material layer fixed with the test piece, peel off the transparent tape from one end of the test piece at a speed of 50 mm / min in a 180° direction, and measure the stress during peeling. Perform the same measurement 5 times, take the average value as the peel strength, and judge using the following criteria.

[0300] Peel strength standard of electrode (positive or negative electrode)

[0301] A: Peel strength is 4N / m or more

[0302] B: Peel strength is 3 N / m or more and less than 4 N / m

[0303] C: Peel strength is 2 N / m or more and less than 3 N / m

[0304] D: Peel strength less than 2N / m

[0305] The separators were collected from the battery cells after the cycle characteristics test, and test pieces were prepared in the same manner. Stress was measured in the same manner as in the (8) separator coating layer peel strength test.

[0306] Separator peel strength criteria

[0307] A: Peel strength is 40N / m or more

[0308] B: Peel strength is 15 N / m or more and less than 40 N / m

[0309] C: Peel strength is 5 N / m or more and less than 15 N / m

[0310] D: Peel strength less than 5N / m

[0311] The larger these values ​​are, the better the bond to the substrate.

[0312] (11) Lithium metal precipitation test

[0313] After the laminated cell type lithium ion secondary battery was injected with electrolyte, it was left to stand at 25°C for 24 hours and then charged to a cell voltage of 4.35V and discharged to a cell voltage of 2.75V using a 0.1C constant current method.

[0314] Next, at -10°C, the battery was charged to a cell voltage of 4.35V (CCCV charging 0.05C cutoff) at 1.5C constant current, and discharged to a cell voltage of 2.75V (CC discharge) at the same rate, and the charge and discharge operation was repeated 5 times. Finally, at 25°C, the battery was charged to a cell voltage of 4.35V at 0.2C constant current.

[0315] After the above operation, the battery cell of the lithium-ion secondary battery is disassembled, the negative electrode is taken out, and the proportion of the lithium metal precipitated portion (Li metal precipitation portion) in the entire negative electrode surface is calculated by image processing. The Li metal precipitation portion is determined based on the color of the electrode surface. Specifically, in the negative electrode facing the positive electrode, the gray to black portion is determined as the Li metal precipitation portion, and the gold portion is determined as the non-precipitation portion.

[0316] A: The proportion of Li metal precipitation is less than 3% of the entire negative electrode surface

[0317] B: The proportion of Li metal precipitation is 3% or more and less than 10% of the entire negative electrode surface.

[0318] C: The proportion of Li metal precipitation is 10% or more and less than 30% of the entire negative electrode surface.

[0319] D: The proportion of Li metal precipitation is more than 30% of the entire negative electrode surface

[0320] The smaller the ratio is, the more the deposition of lithium metal in the negative electrode of the lithium ion secondary battery is suppressed.

[0321] <Example 1>

[0322] The binder composition, negative electrode, separator, and secondary battery of Example 1 were prepared as follows.

[0323] [Preparation of core polymer]

[0324] In a 5 MPa pressure-resistant container A with a stirrer, 33 parts of methyl methacrylate, 33 parts of n-butyl acrylate (butyl acrylate in Table 1), 31 parts of 1,3-butadiene (butadiene in Table 1), 3 parts of methacrylic acid, 2 parts of sodium lauryl sulfate as an emulsifier, 400 parts of ion exchange water, 0.5 parts of tert-dodecyl mercaptan as a chain transfer agent, and 1.0 parts of ammonium persulfate as a polymerization initiator were added, and after sufficient stirring, the mixture was heated to 55° C. to initiate polymerization, and the mixture was reacted for 4 hours, and then the temperature was raised to 70° C. and the mixture was reacted for another 4 hours to obtain a core polymer. The solution of the core polymer was used in the determination of the amount of THF insoluble components.

[0325] [Preparation of mixture for preparing shell polymer]

[0326] In a 5 MPa pressure-resistant container B equipped with a stirrer, 0.35 parts of sodium lauryl sulfate as an emulsifier, 67 parts of ion exchange water, 15 parts of ethyl acrylate as a monofunctional unsaturated carboxylic acid ester monomer, 14.6 parts of n-butyl acrylate (butyl acrylate in Table 1), 12.9 parts of methacrylic acid as a monofunctional unsaturated carboxylic acid monomer, 0.43 parts of ethylene glycol dimethacrylate as a monomer having two or more vinyl functional groups, and 0.1 parts of tert-dodecyl mercaptan as a chain transfer agent were added, and stirred at a temperature of 25° C. for 30 minutes to obtain a mixture for preparing a shell polymer. In the measurement of the weight average molecular weight of the shell, a solution of a single shell polymer is a solution obtained by adding 0.5 parts of ammonium persulfate as a polymerization initiator to a mixture system without a core, polymerizing it at a temperature of 75° C. for 3 hours, and then adding a 5% sodium hydroxide aqueous solution to adjust the pH to 8.

[0327] [Preparation of a binder composition containing core-shell particles]

[0328] After the core polymer reaction, the 5 MPa pressure vessel A equipped with a stirrer was heated to 75° C. The mixture for preparing the shell polymer obtained as described above was added to the pressure vessel A over 3 hours, and at the same time, 0.5 parts of ammonium persulfate as a polymerization initiator was added to the pressure vessel A to initiate shell polymerization.

[0329] After 3 hours from the initiation of the shell polymerization, the addition of the entire amount of the mixture was completed. Then, the mixture was heated to 85°C, reacted for 4 hours, and cooled to terminate the reaction. The polymerization conversion rate at termination was 97%. As the unneutralized solution after polymerization in the determination of the viscosity ratio of the binder composition before and after neutralization, the solution of the reactant was used.

[0330] A 5% sodium hydroxide aqueous solution was added to the above-mentioned reaction product solution to adjust the pH from 2.5 to 8.0. In the measurement of the viscosity ratio of the binder composition before / after neutralization, the viscosity after neutralization was measured on the solution of the reaction product adjusted to a solid content concentration of 10%.

[0331] Then, the unreacted monomers were removed by heating and distilling under reduced pressure, and then further cooled to obtain a binder composition.

[0332] The obtained binder composition contains core-shell type particles, and the monomer compositions of the core and shell parts thereof are as follows, which are substantially the same as the monomer unit composition in the polymer.

[0333] In 100% of the core monomer, methyl methacrylate accounted for 33%, n-butyl acrylate accounted for 33%, 1,3-butadiene accounted for 31%, and methacrylic acid accounted for 3%.

[0334] In 100% of the shell monomer, ethyl acrylate accounted for 35%, n-butyl acrylate accounted for 34%, methacrylic acid accounted for 30%, and ethylene glycol dimethacrylate accounted for 1%.

[0335] The ratio of the mass of the core portion to the mass of the shell portion (mass of the core portion / mass of the shell portion) was 70 / 30.

[0336] [Preparation of slurry composition for secondary battery]

[0337] In a planetary mixer, 98 parts of electrode active material with a specific surface area of ​​3.5 m 2 / g of artificial graphite (volume average particle size: 25μm), 1.0 part of sodium carboxymethyl cellulose (etherification degree: 1.0, aqueous solution viscosity at solid content concentration of 1.0%: 2500mPa·s), adjusted to a solid content concentration of 58% with ion exchange water, and mixed at 45rpm for 60 minutes at room temperature (25°C). Next, dilute with ion exchange water in two stages to a solid content concentration of 53% and 50%. (Mixed at 45rpm for 15 minutes respectively). Furthermore, add 1.0 part of a binder composition in terms of solid content and mix at 45rpm for 15 minutes.

[0338] The obtained mixture was deaerated at 10 rpm for 3 minutes under a reduced pressure of -0.09 MPa or less to obtain a slurry composition for a secondary battery. The obtained slurry composition had excellent fluidity. The slurry composition for a secondary battery was used in a foaming test of the slurry composition.

[0339] [Negative electrode (prepared using the slurry composition for secondary battery of the present invention)]

[0340] The slurry composition for secondary batteries was applied on a copper foil (current collector) with a thickness of 18 μm using a notch wheel coater to a film thickness of 105 μm after drying and a coating amount of 10 mg / cm 2 The copper foil coated with the composition was conveyed in an oven at 75°C for 2 minutes at a speed of 0.5 m / min, and further conveyed in an oven at 120°C for 2 minutes, thereby drying the composition on the copper foil to obtain a negative electrode raw material. The negative electrode raw material was rolled by rolling to obtain a negative electrode with a negative electrode composite material layer having a thickness of 80 μm.

[0341] [Manufacturing of Secondary Batteries]

[0342] In a planetary mixer, add 95 parts of LiCoO2 with a spinel structure as a positive electrode active material, 3 parts of PVDF (polyvinylidene fluoride) as a binder for the positive electrode composite material layer in terms of solid content, 2 parts of acetylene black as a conductive material, and 20 parts of N-methylpyrrolidone as a solvent, and mix.

[0343] The obtained composition is coated on an aluminum foil (current collector) with a thickness of 20 μm using a notch wheel coater so that the film thickness after drying is about 100 μm. The aluminum foil coated with the composition is transported in an oven at a temperature of 60°C for 2 minutes at a speed of 0.5 m / min, and further transported in an oven at a temperature of 120°C for 2 minutes, thereby drying the composition on the aluminum foil to obtain a positive electrode raw material. The positive electrode raw material is rolled by rolling to obtain a positive electrode with a thickness of 70 μm for the positive electrode composite material layer. A secondary battery is made using the obtained positive electrode.

[0344] A single-layer polypropylene separator (width 65 mm, length 500 mm, thickness 25 μm; produced by a dry process; porosity 55%) was cut into a 5 cm×5 cm square and used to prepare a secondary battery.

[0345] Prepare an aluminum package as the outer package of the battery. Cut the above-mentioned positive electrode into a 4cm×4cm square and arrange it in such a way that the surface on the collector side is in contact with the aluminum package. Next, arrange the above-mentioned square spacer on the surface of the positive electrode composite material layer of the positive electrode. Furthermore, cut the above-mentioned negative electrode into a 4.2cm×4.2cm square and arrange it on the spacer in such a way that the surface on the negative electrode composite material layer side is opposite to the spacer. Next, as an electrolyte, fill with a LiPF6 solution with a concentration of 1.0M (the solvent is a mixed solvent of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 30 / 70 (volume ratio), containing 2 volume % (solvent ratio) of vinylene carbonate as an additive). Furthermore, in order to seal the opening of the aluminum package, heat sealing at 150°C is performed to seal the aluminum package to manufacture a laminated battery unit type lithium ion secondary battery.

[0346] <Examples 2 to 11, 26, Comparative Examples 1 to 8>

[0347] When preparing the shell part, the composition ratio and type of the shell part monomer were changed as shown in Table 1. Except for this, the binder composition, the slurry composition for secondary battery, the negative electrode and the secondary battery were prepared in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1. The ethoxylated pentaerythritol tetraacrylate used in Example 9 and Comparative Example 8 was manufactured by Shin Nippon Chemical Industry Co., Ltd., and the product name is ATM35E.

[0348] <Examples 12 and 13>

[0349] The binder composition, the slurry composition for secondary batteries, the negative electrode and the secondary battery were prepared in the same manner as in Example 1, except that the amount of tert-dodecyl mercaptan (0.5 parts) used as a chain transfer agent when preparing the core part was changed to 0.9 parts in Example 12 and to 0.05 parts in Example 13. Then, various evaluations were performed in the same manner as in Example 1.

[0350] <Examples 14 to 17, Comparative Examples 9 and 10>

[0351] The addition amounts of the core and the shell were adjusted, and the ratio of the mass of the core to the mass of the shell (mass of the core / mass of the shell) was changed to that shown in Table 1. A binder composition, a slurry composition for a secondary battery, a negative electrode, and a secondary battery were prepared in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1.

[0352] <Examples 18 to 20>

[0353] For the binder composition of Example 1, the SBR binder was blended at the mass ratio shown in Table 1 (the solid content equivalent of the binder in the binder composition was the same as that in Example 1), and the slurry composition for secondary batteries, the negative electrode and the secondary battery were manufactured in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1.

[0354] The SBR binder used was prepared as follows.

[0355] In a 5 MPa pressure-resistant container A equipped with a stirrer, 3.15 parts of styrene, 1.66 parts of 1,3-butadiene, 0.19 parts of itaconic acid, 0.2 parts of sodium lauryl sulfate as an emulsifier, 20 parts of ion exchange water, and 0.03 parts of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the mixture was heated to 60° C. to initiate polymerization, and the mixture was reacted for 6 hours to obtain seed particles.

[0356] After the above reaction, heating to a temperature of 75° C. was started, and 58.85 parts of styrene as an aromatic monomer, 33.34 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 0.81 parts of itaconic acid as other monomers, 1 part of methyl methacrylate as a (meth)acrylate monomer as other monomers, 0.25 parts of tert-dodecyl mercaptan as a chain transfer agent, and 0.35 parts of sodium lauryl sulfate as an emulsifier were added to the pressure vessel A. At the same time, 1 part of potassium persulfate as a polymerization initiator was started to be added to the pressure vessel A, thereby initiating the second stage polymerization.

[0357] Furthermore, 4 hours after the initiation of the second stage polymerization (after 70% of the total monomer composition was added), 1 part of 2-hydroxyethyl acrylate as another monomer was added to the pressure vessel A over 1 hour and 30 minutes.

[0358] That is, as the total monomer composition, 62 parts of styrene, 35 parts of 1,3-butadiene, 1 part of itaconic acid, 1 part of 2-hydroxyethyl acrylate, and 1 part of methyl methacrylate as another monomer were used.

[0359] After 5 and a half hours from the start of the second stage polymerization, the entire amount of the mixture containing these monomer compositions was added, and then the temperature was further heated to 85° C. and reacted for 6 hours.

[0360] When the polymerization conversion rate reaches 97%, the reaction is terminated by cooling. A 5% sodium hydroxide aqueous solution is added to the mixture containing the polymer to adjust the pH to 8. Then, unreacted monomers are removed by heating and distilling under reduced pressure. Then, the mixture is further cooled to prepare an SBR binder.

[0361] <Example 21>

[0362] The binder composition of Example 1 was blended with an SBS binder at a mass ratio shown in Table 1 (the solid content equivalent of the binder in the binder composition was the same as that in Example 1), and a secondary battery slurry, a negative electrode, and a secondary battery were manufactured in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1.

[0363] The SBS binder used was prepared as follows.

[0364] [Preparation of Cyclohexane Solution of Block Polymer]

[0365] In a pressure-resistant reactor, 233.3 kg of cyclohexane, 54.2 mmol of N,N,N',N'-tetramethylethylenediamine (hereinafter referred to as "TMEDA"), and 30.0 kg of styrene as an aromatic vinyl monomer were added. Then, they were stirred at a temperature of 40°C, 1806.5 mmol of n-butyl lithium as a polymerization initiator was added, and polymerization was carried out for 1 hour while the temperature was raised to 50°C. The polymerization conversion rate of styrene was 100%.

[0366] Next, the temperature was controlled to maintain at 50 to 60° C., and 70.0 kg of 1,3-butadiene as an aliphatic conjugated diene monomer was continuously added to the pressure-resistant reactor over 1 hour. After the addition of 1,3-butadiene was completed, the polymerization reaction was further continued for 1 hour. The polymerization conversion rate of 1,3-butadiene was 100%.

[0367] Next, 722.6 mmol of dichlorodimethylsilane as a coupling agent was added to the pressure-resistant reactor, and a coupling reaction was performed for 2 hours to form a styrene-butadiene coupling block copolymer.

[0368] Then, in order to inactivate the active terminal, 3612.9 mmol of methanol was added to the reaction solution and mixed thoroughly.

[0369] Next, 0.05 parts of 4-[[4,6-bis(octylthio)-1,3,5-triazin-2-yl]amino]-2,6-di-tert-butylphenol (H1) as a hindered phenol-based antioxidant and 0.09 parts of 3,9-bis(octadecyloxy)-2,4,8,10-tetraoxa-3,9-diphosphospiro[5.5]undecane (P1) as a phosphite-based antioxidant were added to 100 parts (containing 30.0 parts of the polymer component) of the reaction solution and mixed.

[0370] The obtained mixed solution was slowly dropped into warm water at a temperature of 85 to 95° C. to volatilize the solvent to obtain a precipitate. Then, the precipitate was pulverized and dried with hot air at a temperature of 85° C. to recover a dry product containing a block polymer.

[0371] Then, the recovered dry product was dissolved in cyclohexane to prepare a block polymer solution having a block polymer concentration of 5.0%.

[0372] [Phase inversion emulsification]

[0373] Sodium alkylbenzene sulfonate was dissolved in ion exchange water to prepare a 0.15% aqueous solution. 1400 g of the obtained aqueous solution and 1000 g of the block polymer solution obtained as described above were placed in a tank and stirred to perform premixing. Next, the premix was transferred from the tank to a high-pressure emulsifying disperser "LAB1000" (manufactured by SPXFLOW) using a metering pump and circulated (passing times: 5 times) to obtain an emulsion formed by phase inversion emulsification of the premix.

[0374] Next, the cyclohexane in the obtained emulsion was distilled off under reduced pressure using a rotary evaporator, and the distilled emulsion was centrifuged at 7000 rpm for 10 minutes using a centrifuge (manufactured by Hitachi Koki Co., Ltd., product name "Himac CR21N"), and the upper layer was taken out and concentrated.

[0375] Finally, the upper layer was filtered through a 100-mesh metal mesh to obtain an aqueous dispersion (block polymer latex) containing particulate block polymers.

[0376] [Graft polymerization and cross-linking]

[0377] Distilled water is added to the obtained block polymer latex for dilution so that the water is 850 parts relative to 100 parts (equivalent to the solid content) of the granular block polymer. The diluted block polymer latex is put into a polymerization reaction vessel with a stirrer replaced by nitrogen, and the temperature is heated to 30°C while stirring. In addition, using another container, 4 parts of methacrylic acid as an acidic group-containing monomer and 15 parts of distilled water are mixed to prepare a methacrylic acid dilution. The methacrylic acid dilution is added to a polymerization reaction vessel heated to a temperature of 30°C for 30 minutes, thereby adding 4 parts of methacrylic acid relative to 100 parts of the block polymer.

[0378] Furthermore, using another container, a solution (g) containing 7 parts of distilled water and 0.01 parts of ferrous sulfate (manufactured by Chubu Chelest Co., Ltd., trade name "Frost Fe") as a reducing agent was prepared. After adding the obtained solution to the polymerization reactor, 0.5 parts of 1,1,3,3-tetramethylbutyl hydroperoxide (manufactured by NOF Corporation, trade name "PEROCTA H") as an oxidant was added, and after reacting it at a temperature of 30°C for 1 hour, it was further reacted at a temperature of 70°C for 2 hours to obtain a reactant. The polymerization conversion rate was 99%. The reactant was used as an SBS binder.

[0379] <Example 22>

[0380] A binder composition, a slurry composition for a secondary battery, a negative electrode, and a secondary battery were prepared in the same manner as in Example 1, except that the thickener used in preparing the slurry composition for a secondary battery was changed from sodium carboxymethyl cellulose to a lithium salt of an acrylic acid / acrylamide / hydroxyethyl acrylamide copolymer. Then, various evaluations were performed in the same manner as in Example 1. The lithium salt of the acrylic acid / acrylamide / hydroxyethyl acrylamide copolymer used was prepared as follows.

[0381] [Preparation of Lithium Salt of Acrylic Acid / Acrylamide / Hydroxyethylacrylamide Copolymer]

[0382] 789 parts of ion exchange water were added to a 1L glass flask, heated to 40°C, and the inside of the flask was replaced with nitrogen at a flow rate of 100 mL / min. Next, 45 parts of acrylamide, 25 parts of acrylic acid, and 30 parts of hydroxyethyl acrylamide were mixed and injected into the flask. Then, 8.9 parts of a 2.5% aqueous solution of potassium persulfate as a polymerization initiator was added to the flask with a syringe. 15 minutes after the addition of the above-mentioned polymerization initiator, 22.2 parts of a 2.0% aqueous solution of tetramethylethylenediamine as a polymerization accelerator was added with a syringe to initiate the polymerization reaction.

[0383] 4 hours after the addition of the polymerization initiator, 4.4 parts of a 2.5% aqueous solution of potassium persulfate as a polymerization initiator and 11 parts of a 2.0% aqueous solution of tetramethylethylenediamine as a polymerization accelerator were added to the flask, and the temperature was raised to 60° C. and maintained to carry out the polymerization reaction. 3 hours after the addition of the polymerization initiator, the flask was opened to the air to terminate the polymerization reaction, and an 8% aqueous solution of lithium hydroxide was added to the obtained polymer, and the mixture was stirred at 80° C. for 6 hours, and the pH was adjusted to 8.0 to obtain a lithium salt of a hydroxyethyl acrylamide-acrylic acid-acrylamide copolymer as a thickener.

[0384] <Example 23>

[0385] The SBR binder used in Example 18 was used as the core polymer solution, and the composition ratio and type of the shell monomer were changed to those shown in Table 1. A binder composition, a secondary battery slurry composition, a negative electrode, and a secondary battery were prepared in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1.

[0386] <Example 24>

[0387] The reaction product of the previous stage of [graft polymerization and crosslinking] of the SBS binder used in Example 21 was used as the core polymer solution, and the composition ratio and type in 100 parts of the shell monomer were changed to those shown in Table 1. A binder composition, a slurry composition for secondary batteries, a negative electrode, and a secondary battery were prepared in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1.

[0388] <Example 25>

[0389] The binder composition, the slurry composition for secondary batteries, the negative electrode and the secondary battery were prepared in the same manner as in Example 1, except that the active material used in the preparation of the slurry composition for secondary batteries was changed from graphite to a graphite-silicon active material (the mass of graphite: the mass of the silicon-based active material SiOx = 70:30), and the thickener was changed from sodium carboxymethylcellulose to a lithium salt of an acrylic acid / acrylamide / hydroxyethylacrylamide copolymer (the same thickener as used in Example 22). Then, various evaluations were performed in the same manner as in Example 1.

[0390] <Example 27>

[0391] The binder composition prepared in Example 1 was used to prepare a separator having a porous membrane layer slurry composition and a porous membrane layer as follows. A secondary battery was prepared in the same manner as in Example 1 except that the separator having the porous membrane was used. Then, various evaluations were performed in the same manner as in Example 1.

[0392] [Preparation of slurry composition for porous membrane layer]

[0393] 100 parts of aluminum oxide (volume average particle size: 0.5 μm) as non-conductive particles, 1.0 parts of polycarboxylic acid ammonium (manufactured by Toagosei, product name "ARONA-6114") as a dispersant, and water were mixed to obtain a mixture. The amount of water was adjusted so that the solid content concentration was 50%. The mixture was treated with a medium-free dispersion device to disperse the aluminum oxide to obtain a dispersion liquid.

[0394] 2.0 parts of sodium salt of carboxymethyl cellulose (etherification degree: 1.0, viscosity of aqueous solution at solid content concentration of 1.0%: 500 mPa·s) was added to the obtained dispersion and mixed. The added sodium salt of carboxymethyl cellulose was dissolved in the mixed solution.

[0395] Next, 5.0 parts (equivalent to the solid content) of the adhesive composition of Example 1 and 0.2 parts of aliphatic polyether-type nonionic surfactant as a wetting agent are added to the mixed liquid, and water is added until the solid content concentration reaches 40% to obtain a slurry composition for a porous membrane layer.

[0396] [Production of a separator having a porous membrane layer]

[0397] A single-layer polypropylene spacer substrate (width 250 mm, length 1000 m, thickness 12 μm) manufactured by a wet method was prepared. Then, the redispersed porous film layer slurry composition was applied to the surfaces on both sides of the spacer substrate using a gravure coating machine (coating speed: 20 m / min) to a thickness of 2.5 μm after drying. Next, the spacer substrate coated with the porous film layer slurry composition was dried in a drying oven at a temperature of 50°C and wound, thereby making a spacer with a porous film layer on both sides of the spacer substrate. The spacer was cut into a square of 5 cm × 5 cm for making a secondary battery.

[0398] The test piece for measuring the peel strength of the separator coating layer was a separator having a porous membrane layer on one surface, prepared in the same manner as above except that the slurry composition for a porous membrane layer was applied on one surface of a separator substrate.

[0399] <Example 28>

[0400] Using the binder composition prepared in Example 1, a positive electrode slurry composition was prepared as follows. The negative electrode slurry composition was prepared in the same manner as the slurry composition for a secondary battery described in Example 1, and the SBR binder described in Examples 18 to 20 was used as the binder composition. A secondary battery was prepared in the same manner as in Example 1 except that these positive electrode slurry compositions and negative electrode slurry compositions were used. Then, various evaluations were performed in the same manner as in Example 1.

[0401] [Preparation of positive electrode slurry composition]

[0402] 100 parts of carbon-coated lithium iron phosphate and 10 parts of acetylene black as a conductive carbon were dry mixed in a sealed container to prepare a powder. 100 parts of a 2% sodium carboxymethyl cellulose aqueous solution (etherification degree: 1.0, aqueous solution viscosity at solid content concentration of 1.0%: 500 mPa·s) as a water-soluble thickener were added to the powder, and the mixture was fully mixed with a planetary mixer to prepare a premixed paste. The obtained premixed paste was dispersed with a bead mill using zirconium oxide beads with a diameter of 1 mmφ, and 3 parts (equivalent to the solid content) of the binder composition of Example 1 were added and fully mixed to obtain a positive electrode slurry composition.

[0403] [Production of positive electrode (using positive electrode slurry composition)]

[0404] The obtained positive electrode slurry composition was applied to a clean aluminum foil current collector using a film coater to a thickness of 120 μm, and then fully dried in a warm air dryer. The drying conditions were 10 minutes in a warm air dryer at 50°C. The dry weight was 10 mg / cm 2 .

[0405] <Comparative Example 11>

[0406] The amount of the shell portion is shown in Table 1. When preparing the shell portion, the amount of tert-dodecyl mercaptan as a chain transfer agent (0.1 parts in Example 1) was changed to 3.5 parts. A binder composition, a slurry composition for a secondary battery, a negative electrode, and a secondary battery were prepared in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1.

[0407] <Comparative Example 12>

[0408] The amount of the shell portion is shown in Table 1. When preparing the shell portion, the amount of tert-dodecyl mercaptan as a chain transfer agent (0.1 part in Example 1) was changed to 0 part, and the amount of ammonium persulfate as a polymerization initiator during the polymerization of the shell portion (0.5 part in Example 1) was changed to 0.1 part. Otherwise, a binder composition, a slurry composition for a secondary battery, a negative electrode, and a secondary battery were prepared in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1. Then, various evaluations were performed in the same manner as in Example 1.

[0409] [Table 1]

[0410]

[0411] *The values ​​under each monomer are the feed amounts (expressed in parts)

[0412] (Continued)

[0413]

[0414] *The values ​​under each monomer are the feed amounts (expressed in parts)

[0415] (Continued)

[0416]

[0417] *The values ​​under each monomer are the feed amounts (expressed in parts)

[0418] (Continued)

[0419]

[0420] *The values ​​under each monomer are the feed amounts (expressed in parts)

[0421] (Continued)

[0422]

[0423] *The values ​​under each monomer are the feed amounts (expressed in parts)

[0424] (Continued)

[0425]

[0426] *The values ​​under each monomer are the feed amounts (expressed in parts)

[0427] (Continued)

[0428]

[0429] *The values ​​under each monomer are the feed amounts (expressed in parts)

[0430] (Continued)

[0431]

[0432] *The number under each monomer is the amount of feed (expressed in parts)

[0433] Industrial Applicability

[0434] According to the secondary battery binder composition of the present invention, a slurry composition for secondary battery, a functional layer for secondary battery, a separator for secondary battery, an electrode for secondary battery, and a secondary battery can be provided. According to the present invention, in the manufacturing process of separators, electrodes, etc. of secondary batteries, excellent adhesion can be achieved between the layer obtained using the binder composition and the substrate, and a secondary battery with good cycle characteristics can be obtained. Even after repeated charge and discharge cycles, the reduction of adhesion is also suppressed. In addition, in lithium ion secondary batteries, the precipitation of lithium metal is significantly suppressed.

Claims

1. A binder composition for a secondary battery, comprising a polymer and a solvent, The polymer is a core-shell type particle having a core portion composed of a polymer (a1) and a shell portion composed of a polymer (a2), The polymer (a1) is a copolymer composed of unsaturated carboxylic acid ester monomer units, unsaturated carboxylic acid monomer units and aliphatic conjugated diene monomer units, an aliphatic conjugated diene polymer or an aromatic vinyl-aliphatic conjugated diene copolymer, The polymer (a2) comprises 50.0% by mass or more and 89.9% by mass or less of a monofunctional unsaturated carboxylic acid ester monomer unit, 10.0% by mass or more and 49.9% by mass or less of one or more monomer units selected from a monofunctional unsaturated carboxylic acid monomer unit and a monofunctional unsaturated sulfonic acid monomer unit, 0.1% by mass or more and 10.0% by mass or less of a monomer unit having two or more vinyl functional groups, and 5.0% by mass or less of an aromatic vinyl monomer unit, The amount of the at least one monomer unit selected from the group consisting of a monofunctional unsaturated carboxylic acid monomer unit and a monofunctional unsaturated sulfonic acid monomer unit is 0.1 mol or more and 15,000 mol or less relative to 1 mol of the monomer unit having two or more vinyl functional groups.

2. The binder composition for secondary batteries according to claim 1, wherein The amount of tetrahydrofuran-insoluble components in the polymer (a1) is 40% or more and 97% or less.

3. The binder composition for secondary batteries according to claim 1 or 2, wherein The ratio of the mass of the polymer (a1) to the mass of the polymer (a2) is 95 / 5 or less and 5 / 95 or more.

4. The binder composition for secondary batteries according to claim 1 or 2, wherein The core-shell type particles have an inertia radius of 10 nm or more and 1000 nm or less. 5 . A slurry composition for a secondary battery, comprising the binder composition for a secondary battery according to claim 1 .

6. The slurry composition for secondary battery according to claim 5, wherein Also included are non-conductive particles.

7. The slurry composition for secondary battery according to claim 5, wherein It also contains electrode active material particles. 8 . A functional layer for a secondary battery, formed using the slurry composition for a secondary battery according to claim 5 . 9 . A separator for a secondary battery, comprising a separator substrate and a functional layer for a secondary battery formed using the slurry composition for a secondary battery according to claim 6 . 10 . An electrode for a secondary battery, comprising a functional layer for a secondary battery formed using the slurry composition for a secondary battery according to claim 7 on a current collector. 11 . A secondary battery comprising the functional layer for a secondary battery according to claim 8 . 12 . A secondary battery comprising the separator for a secondary battery according to claim 9 . 13 . A secondary battery comprising the secondary battery electrode according to claim 10 .

Citation Information

Patent Citations

  • Image sensor

    JP1994302797A

  • Battery electrode binder

    JP1999025989A

  • Binder for lithium secondary batteries that has a two-phase structure or more with controlled battery properties, adhesiveness, and coating properties

    JP2006513554A

  • Binder for battery electrode, and electrode for lithium secondary battery comprising the same

    JP2013073921A

  • Electrochemical device electrode binder

    JP2013182765A